Proceedings of the International Conference on Advanced Visual Interfaces 2020
DOI: 10.1145/3399715.3399827
|View full text |Cite
|
Sign up to set email alerts
|

Visual Encodings for Networks with Multiple Edge Types

Abstract: Figure 1: Examples of visual designs considered for encoding multiple types of edges in matrices. The top row shows an example of a single matrix and the bottom row shows the encoding for each edge type. The encodings use one or more visual variables to represent multiple edges: a) uses a coloured pie chart, b) uses opacity in a pie chart, c) uses a segmented and coloured pie chart d) uses orientation, e) combines position and colour, f) uses size and g) combines size and colour to create a glyph. The designs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In this section, we discuss insights gained from understanding what is being evaluated across multiple evaluation studies. In the current literature on DMVNs, evaluation studies are mainly focused on node‐link diagrams [AP12,FM16,LAN20], while very few studied matrix‐based visualizations [VABK20] and compared both techniques [FAM21]. List views are not yet evaluated for their effectiveness in visual exploration and analysis of DMVNs.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we discuss insights gained from understanding what is being evaluated across multiple evaluation studies. In the current literature on DMVNs, evaluation studies are mainly focused on node‐link diagrams [AP12,FM16,LAN20], while very few studied matrix‐based visualizations [VABK20] and compared both techniques [FAM21]. List views are not yet evaluated for their effectiveness in visual exploration and analysis of DMVNs.…”
Section: Discussionmentioning
confidence: 99%
“…adjacency matrices) present significant potential for multi‐variate network visualization. Similarly, a limited number of techniques investigate the visualization of edge attributes: tabular and integrated approaches could be potential areas where this challenge can be tackled [ SSE16 , VABK20 ]. The evaluation analysis shows that very few studies rigorously investigated the trade‐offs and benefits of different multi‐variate visualization techniques – task taxonomies have the potential and purpose to drive more formal evaluations.…”
Section: Surveysmentioning
confidence: 99%
“…Büschel et al investigated the influence of the edge encoding in AR on task performance, concluding that in general different styles can be used [14]. Vogogias et al [62] investigated designs for encoding multiple types of edges in matrices and found task-dependent performance differences. Soni et al and Kypridemou et al investigated the influence of different layout methods on the perception of graph properties in 2D [43,59].…”
Section: Network Comparison and Visualization Metaphorsmentioning
confidence: 99%